Research on Diversity in Youth Literature, edited by Sarah Park Dahlen and Gabrielle Atwood Halko - Terri Suico (University of Oklahoma Libraries, 2020)
Terri Suico reviews the bi-annual journal, Research on Diversity in Youth Literature, edited by Sarah Park Dahlen and Gabrielle Atwood Halko.